Relationship between Trade Openness, Financial Development and Economic Growth of Nepal: Evidence from a Developing Country (Quest Journal of Management and Social Sciences, 2020)
Background: Capital investment, financial and technological developments are essential drivers for the economic growth of developing countries like Nepal. These factors, directly and indirectly, contribute to the growth of the country. Technological factors such as FDI and trade allow technology and knowledge transfers to Nepal along with foreign investments, goods and services. The financial sector encourages investors by providing loans that further generates investment in the country. Similarly, the development of human capital further increases labor productivity. Nepal, being a developing country, lacks advanced infrastructure and technology, that are vital for pushing the economic growth in the country.Objective: This paper examined the effect of capital, labor, foreign direct investment, financial development and trade on the economic growth of Nepal using the endogenous growth model.Methods: The study employedthe ARDLboundstesting approach to test the long-run relationships introducing an error correction model to estimate both short and long-term relationships among the variables.The TY non-granger causality test was used to ensure robustness and check the direction of causality.Results: The results showed that gross fixed capital formation, population and financial development were significant and inducedpositive economic growth in the long run at a 1% level of significance whereas, the impact of FDI on economic growth was negative and significant at 1%.Conclusions: The study concludes that an increase in gross fixed capital formation, population and broad money supply positively impacts the economic growth of Nepal. However, technological factors such as FDI and trade do not adequately explain the economic growth due to low FDI inflows, political instability, poor infrastructure and import dependency.Implications: The study emphasized domestic investment and financial development of the country as they were found to be highly significant in the long run. Also, the human capital of the country should be developed by providing education and training as the population was found to be highly significant. The study also indicated that Nepal should push export as its share in the trade is very less. Moreover, policies such as legal reforms, incentives to foreign investors and infrastructural development to attract FDIs in Nepal should be formulated.